PUBLIC OPINION ON NOISE DISTURBANCE DUE TO THE ACTIVITIES OF HUSEIN SASTRANEGARA AIRPORT, BANDUNG, INDONESIA - Lili Mulyatna; Yonik Meilawati Yustiani; Pebby Febrianto (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2021)
Airport is a facility to accommodate arrivals and departures as well as aircraft movements that have the potential to cause noise impacts. This research was conducted to obtain opinions from the public regarding the noise that occurs around Husein Sastranegara Airport, Bandung, Indonesia. In addition, the determination of the airport noise area was also carried out using the Weighted Equivalent Continuous Perceived Noise Level (WECPNL) method. There are 12 measurement points, namely at distances of 100 m, 500 m, and 1500 m in each of the North, East, South, and West directions. Opinions regarding the noise that occurred were obtained from 150 respondents from the community around the airport. The results of the study can be concluded that the highest WECPNL index value is found on the 100 m runway, the WECPNL index value is 76.39, the 500 m distance the WECPNL index value is 62.71, and the 1500 m distance the WECPNL index value is 52.74. The results of the WECPNL index at Husein Sastranegara International Airport Bandung have a level 2 noise area where school buildings and settlements should not be allowed. The results of the interviews show that as many as 54% of respondents feel disturbed by the noise caused by the activities of Husein Sastranegara Airport.